Plant peroxisome proteostasis—establishing, renovating, and dismantling the peroxisomal proteome. Issue 2 (5th August 2022) - Muhammad, DurreShahwar; Smith, Kathryn A.; Bartel, Bonnie
Abstract: Plant peroxisomes host critical metabolic reactions and insulate the rest of the cell from reactive byproducts. The specialization of peroxisomal reactions is rooted in how the organelle modulates its proteome to be suitable for the tissue, environment, and developmental stage of the organism. The story of plant peroxisomal proteostasis begins with transcriptional regulation of peroxisomal protein genes and the synthesis, trafficking, import, and folding of peroxisomal proteins. The saga continues with assembly and disaggregation by chaperones and degradation via proteases or the proteasome. The story concludes with organelle recycling via autophagy. Some of these processes as well as the proteins that facilitate them are peroxisome-specific, while others are shared among organelles. Our understanding of translational regulation of plant peroxisomal protein transcripts and proteins necessary for pexophagy remain based in findings from other models. Recent strides to elucidate transcriptional control, membrane dynamics, protein trafficking, and conditions that induce peroxisome turnover have expanded our knowledge of plant peroxisomal proteostasis. Here we review our current understanding of the processes and proteins necessary for plant peroxisome proteostasis—the emergence, maintenance, and clearance of the peroxisomal proteome.